The master triathlete - Lepers, R. (Triathlon Medicine, 2019)
Age-related changes in physiology of master triathletes (i.e. >40 years old) result inevitably in a decrease in triathlon performance. The increase in participation of master triathletes in short- and long-distance triathlons over the last decades has been accompanied by an improvement in their performances at a faster rate than their younger counterparts. Age-related declines in triathlon performance depend upon the discipline (swimming, cycling or running), the event duration (short versus long distance), the type of triathlon (road-based versus off-road triathlon) and sex of the participant. Reductions in the maximal oxygen consumption (VO2max), blood lactate threshold and submaximal exercise economy all contribute to the decrease in triathlon performance with advancing age, but VO2max appears to be the parameter that is the most altered by age. Master triathletes may require greater recovery durations between training sessions to allow optimal both physical and psychological recovery. Further studies investigating different training regimes (e.g. concurrent strength and aerobic training, high-intensity interval training), recovery capacities, nutrition habits and psychology of master triathletes are needed to gain better insights on age-related declines in triathlon performance.